El tabaquismo y su incidencia en la enfermedad pulmonar obstructiva crónica en pacientes masculinos de 60 a 70 años en el Hospital Abel Gilbert Portón, Guayaquil diciembre - abril 2023 - Romero Fariño, Erik Andrés (2023)
The present study investigated the relationship between smoking and chronic obstructive pulmonary disease in male patients aged 60 to 70 years at the Abel Gilbert Pontón Hospital in Guayaquil, during the month of December to April 2023, the relationship between smoking and chronic obstructive pulmonary disease. The purpose of this study was to see how smoking affects chronic obstructive disease in older adults. One of the tools used in this study is the deductive method, we analyze this research and specific and clear information is provided to raise awareness among patients who are at the Abel Gilbert Pontón Hospital. The objective of the research is to sensitize the population to prevent Chronic Obstructive Disease and its mortality, offering educational information to both young people and older adults.